The role of academic achievement in mathematically predicting licensure examination for teachers outcomes: Insights from secondary education graduates - Makiling, Rodillo; Christian G. Abalos; Ma. Leah I. Abad; Jomar C. Cabuquin (Universitas Hamzanwadi, 2025)
The successful passing of the Licensure Examination for Teachers (LET) by secondary education graduates is one of the core priorities of Tertiary Education Institutions (TEIs) in the Philippines, as they work to address the increasing demands of the teaching workforce and produce highly qualified educators. However, few studies have attempted to create a model to predict the probability of passing LET. In this study, a quantitative approach using a predictive-correlational design was used to analyze the correlations between areas of academic achievement and LET performance among Bachelor of Secondary Education (BSEd) graduates at a government-funded university in the Leyte province. This study also investigated the role of academic achievement in predicting BSEd graduates’ licensure examination performances. Using total enumeration sampling, 225 BSEd graduates’ academic achievement records and LET performances were considered. The results revealed significant correlations between the areas of academic achievement and licensure examination performance among BSEd graduates. Meanwhile, achievements in professional education courses followed by general education courses were the most significant predictors of LET performance. This result implies that BSEd graduates aiming to excel in LET should prioritize strong performance in their professional and general education courses during their studies, as it could significantly impact LET outcomes.